Table S2 from Proteomic Profiling of Extracellular Matrix Components from Patient Metastases Identifies Consistently Elevated Proteins for Developing Nanobodies That Target Primary Tumors and Metastases - Noor Jailkhani (16015810) (2025)
Supplementary Table S2